Chapter 10 Análisis no-lineal de materiales compuestos mediante la teoría de mezclas serie-paralelo - Rastellini, Fernando (OmniaScience, 2014)
This chapter presents the theory of series-parallel mixtures. This is a formulation for the simulation of the mechanical behavior of composite materials, which allows to obtain the non-linear behavior of the same from the behavior that show their component materials. This formulation can be applied to both compounds Laminates of carbon fibers as to more traditional composite materials such as reinforced concrete. The validity of the submitted formulation will be tested with the reproduction of a delamination test of a laminated composite. The advantage of the series-parallel mixing theory versus other existing formulations for the calculation of composite materials is that this is, today, the only one capable of taking into account the non-linear behavior of the compounds with a computational cost that makes possible the resolution of real structures.